2017
DOI: 10.1002/soej.12211
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Healthcare Regulation: The Effect of Political Spending on Occupational Licensing Laws

Abstract: Using data on political spending in state elections, this study considers the role of political contributions by healthcare professional interest groups in states' decisions to enact occupational licensing laws. These laws govern how different professions may operate in healthcare markets, and while they ostensibly exist to protect consumers, licensing laws can also insulate professionals from competition in healthcare markets. Higher political spending by physician interest groups increases the probability th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Prior work suggests that NP and PA licensing laws respond to changes in political spending by interest groups connected to physicians and hospitals, with groups connected to NPs playing a small role (McMichael ). The evidence further suggests that political spending is driven by factors other than the size of the professions that are connected to interest groups, that is, provider supply does not drive political spending (McMichael ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work suggests that NP and PA licensing laws respond to changes in political spending by interest groups connected to physicians and hospitals, with groups connected to NPs playing a small role (McMichael ). The evidence further suggests that political spending is driven by factors other than the size of the professions that are connected to interest groups, that is, provider supply does not drive political spending (McMichael ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work suggests that NP and PA licensing laws respond to changes in political spending by interest groups connected to physicians and hospitals, with groups connected to NPs playing a small role (McMichael ). The evidence further suggests that political spending is driven by factors other than the size of the professions that are connected to interest groups, that is, provider supply does not drive political spending (McMichael ). Other investigations into the causes of changes to licensing laws have similarly suggested that lobbying and other political efforts are primarily responsible (see Traczynski & Udalova ; Safriet ; Isaacs & Jellinek ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work suggests that NP and PA licensing laws respond to changes in political spending by interest groups connected to physicians and hospitals, with groups connected to NPs playing a small role (McMichael 2017). The evidence further suggests that political spending is driven by factors other than the size of the professions that are connected to interest groups, that is, provider supply does not drive political spending (McMichael 2017). Other investigations into the causes of changes to licensing laws have similarly suggested that lobbying and other political efforts are primarily responsible (see Traczynski & Udalova 2018;Safriet 2002;Isaacs & Jellinek 2013).…”
Section: B Robustness and Sensitivitymentioning
confidence: 95%
“…For a more complete discussion of the potential effects of NC Board going forward, see Allensworth (2017). For a discussion of the political factors that influence NP and PA licensing laws, see McMichael (2017).…”
Section: Introductionmentioning
confidence: 99%